Pengaruh Penerapan Socratic Method Berbasis Padlet Terhadap Kemampuan Berpikir Kritis Peserta Didik: Pengaruh Penerapan Socratic Method Berbasis Padlet Terhadap Kemampuan Berpikir Kritis Peserta Didik - Iskandar, Nadya Leony; Alamsyah, Trian Pamungkas; Resti, Vica Dian Aprelia (UNIB Press, 2025)
This research aimed to evaluate the effect of applying the Socratic Method based on the Padlet platform on students' critical thinking abilities. This research used a quantitative approach with a quasi-experimental design, pretest-posttest control group type. The research subjects were class IX students of SMP Muhammadiyah 4 Tangerang. The instruments used were essay questions to measure critical thinking skills and observation sheets to assess the implementation of learning. The results of the analysis show that there was a significant difference between the posttest scores of the experimental group and the control group, which is indicated by a significance value of 0.000 (p < 0.05). Apart from that, the average N-Gain score achieved by the experimental group was 0.8, which is in the high category. These findings indicate that the integration of the Socratic Method with Padlet can significantly improve students' critical thinking abilities. Thus, this learning method is worthy of consideration as an alternative strategy in the learning process, especially in developing critical thinking skills at the secondary education level.